2020
DOI: 10.2196/16286
|View full text |Cite
|
Sign up to set email alerts
|

Closing the Digital Divide in Speech, Language, and Cognitive Therapy: Cohort Study of the Factors Associated With Technology Usage for Rehabilitation

Abstract: Background For stroke, traumatic brain injury (TBI), and other neurologic conditions associated with speech-language disorders, speech and language therapy is the standard of care for promoting recovery. However, barriers such as clinician time constraints and insurance reimbursement can inhibit a patient’s ability to receive the support needed to optimize functional gain. Although digital rehabilitation has the potential to increase access to therapy by allowing patients to practice at home, the c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
22
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(27 citation statements)
references
References 29 publications
1
22
0
4
Order By: Relevance
“…Rural participants are less likely to have regular access to the internet or manage personal health information online and email health care providers in the United States [ 31 ]. However, it has been found that rural patients engage digital rehabilitation means more than urban patients [ 32 ]. In Sweden, primary care choice reform in 2010 seemed to have negative effects on geographic equity; the effects do not appear to be very large but they concern some indicators of socioeconomically less advantaged areas [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Rural participants are less likely to have regular access to the internet or manage personal health information online and email health care providers in the United States [ 31 ]. However, it has been found that rural patients engage digital rehabilitation means more than urban patients [ 32 ]. In Sweden, primary care choice reform in 2010 seemed to have negative effects on geographic equity; the effects do not appear to be very large but they concern some indicators of socioeconomically less advantaged areas [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…As the availability of mobile technology increases, apps designed for mobile phones and tablets are increasingly of interest for such therapy. Apps have been developed to identify the presence of aphasia (language impairment) and improve language outcomes [ 14 , 15 ], facilitate homework completion in adults with stroke and TBI [ 16 , 17 ], and improve cognitive skills in adults with acquired cognitive disorders [ 18 ]. In a recent cohort study by Munoz et al [ 16 ], adults with stroke and TBI used an app targeting speech, language, and cognitive skills.…”
Section: Introductionmentioning
confidence: 99%
“…Nowadays, the scientific developments in the field of artificial intelligence are considered the most promising in solving the problem of physical immortality of a human. Great hopes are pinned here on the predicted progress in microelectronics, due to which, as it is believed, there will be an opportunity for the full transfer of human consciousness to an inorganic carrier (Munsell et al, 2020).…”
Section: Homo Virtualismentioning
confidence: 99%